Influence of Flexible Work Practices on Employee Performance in Institutions of Higher Learning in Kenya: A Case of Selected Universities in Nyeri County - N. Dikirr , Sammy; Omuya , Jacqueline (African Journal of Education,Science and Technology (AJEST), 2023)
Work flexibility offers employees a balance between their professional and personal lives, leading to job satisfaction and high performance and an overall improvement of the organization as a whole. Work flexibility is very important, and with digital advancements and improved technology, employees are able to continue their work anywhere they wish, provided they have an internet connection. The general objective was to examine the influence of flexible work practices on employee performance in institutions of higher learning in Nyeri County, Kenya. The study was anchored on Self-determination theory, Three Stage Model for Talent Management and Spill Over Theory. This study employed a descriptive research design. The target population for the study was 1300 staff of Karatina University and Dedan Kimathi University. The study applied stratified random sampling to sample 260 staff. The study used questionnaires to collect data. A pilot was conducted with 10% of the sample size hence 26 staff. Content validity was tested using factor loadings. Cronbach’s Alpha Coefficient method was used to check reliability. Quantitative data was analyzed using descriptive (frequency, percentage, mean,) and inferential statistics (correlation and regression) with the help of SPSS version 28. Data was tabulated and presented in tables. Ethics were observed before, during, and after data collection. Findings show that; there is a strong significant relationship between flexi time and employee performance (r=0.467, p=0.005), a moderate significant relationship between leave and employee performance (r=0.348, p=0.000), a weak significant relationship between tele-working and employee performance (r=0.240, p=0.000), and a strong significant relationship between job sharing and employee performance (r=0.511, p=0.022). The study recommends that; the institutions should embrace flexibility in relation to the work schedules of the staff, the institutions should come up with policies that will guide on how to compensate staff who are recalled to work while on leave, the institutions should organize training for the staff especially on use of technology, the management should also establish a culture that promotes sharing and have proper plans for conducting orientations and inductions to ensure effective onboarding of new personnel.